2007
DOI: 10.1002/cyto.a.20515
|View full text |Cite
|
Sign up to set email alerts
|

Automated classification of bacterial particles in flow by multiangle scatter measurement and support vector machine classifier

Abstract: Biological microparticles, including bacteria, scatter light in all directions when illuminated. The complex scatter pattern is dependent on particle size, shape, refraction index, density, and morphology. Commercial flow cytometers allow measurement of scattered light intensity at forward and perpendicular (side) angles (28 y 1 208 and 708 y 2 1108, respectively) with a speed varying from 10 to 10,000 particles per second. The choice of angle is dictated by the fact that scattered light in the forward region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 54 publications
0
45
0
Order By: Relevance
“…The coarse angular resolution of the MARDI system strongly implies that gathered light is mainly from the main lobe of the bacterium's scattering profile. This is a good indication that unique spectral features are likely due to the size, shape, and bulk refractive index of the bacteria [7,8,10]. This is confirmed in part by the result that stripping the cell membrane of P. aeruginosa had only minor effects on scattering spectrum (Fig.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The coarse angular resolution of the MARDI system strongly implies that gathered light is mainly from the main lobe of the bacterium's scattering profile. This is a good indication that unique spectral features are likely due to the size, shape, and bulk refractive index of the bacteria [7,8,10]. This is confirmed in part by the result that stripping the cell membrane of P. aeruginosa had only minor effects on scattering spectrum (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…Angle-resolved flow cytometry systems are inherently complex and expensive, requiring complex optics to achieve sufficient angular resolution. More recently, systems with fewer channels have been explored in conjunction with more sophisticated machine learning algorithms [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that forward scatter and side scatter can be used to identify a number of cell subpopulation since forward scattering is proportional to the diameter of the cell and side scattering with perpendicular light scatter is also sensitive to small internal structure and to refractive index change 26 . In addition, the scattering is also a function of wavelength 31 .…”
Section: Dual Multi-angle Light Scattering For Cryptosporidium Detectionmentioning
confidence: 99%
“…Light scattering techniques are widely used to investigate the particle properties such as such as size [14][15][16] , refractive index [17][18] and concentration [19][20] and also applied to biological particle detection [21][22][23][24][25][26] as its advantages; easy to perform; low maintenance; non-invasive; have high sensitivity; and the potential for real-time detection.…”
Section: Introductionmentioning
confidence: 99%
“…Not only different bacterial cells in FCM but colonies of different bacterial strains by scattered light and automated image recognition are distinguished (51,52). Light scatter differences reflect unique colony morphotypes and consequently interspecies differences and thus a new diagnostic tool.…”
Section: New Developments and Applications In Flow Andmentioning
confidence: 99%